The challenge of the black middle-class men in negotiating the elusive masculine identities - Nkosi, Thokozani Samuel (My University, 2017)
The study investigated the challenges that black middle class men experience in negotiating the masculine identities within the South African context. The adopted understanding was that of Connell in that there are many ways of being a man. The findings were that men are given a standard or expectations to live by but there are never guided on how to go about meeting them. This was portrayed by the interwoven themes and discourse that in some instances work against each other and render the black middle class men vulnerable in terms of identities.
Research Report: Masters in psychology - Coursework and research report , 07 June 2017
Keywords: Masculinity--South Africa; Men--South Africa--Psychology; Identity (Psychology)--South Africa; Blacks--Social conditions; Middle class men--South Africa